New Provider Models for Sweden and Spain: Public, Private or Non-profit?; Comment on "Governance, Government, and the Search for New Provider Models" - Patrick P.T. Jeurissen; Hans Maarse (Kerman University of Medical Sciences, 2016)
Sweden and Spain experiment with different provider models to reform healthcare provision. Both models have in common that they extend the role of the for-profit sector in healthcare. As the analysis of Saltman and Duran demonstrates, privatisation is an ambiguous and contested strategy that is used for quite different purposes. In our comment, we emphasize that their analysis leaves questions open on the consequences of privatisation for the performance of healthcare and the role of the public sector in healthcare provision. Furthermore, we briefly address the absence of the option of healthcare provision by not-for-profit providers in the privatisation strategy of Sweden and Spain.